The interplay between molecular layering and clustering in adsorption of gases on graphitized thermal carbon black - Spill-over phenomenon and the important role of strong sites - Do, D.; Tan, S.; Zeng, Y.; Fan, Chunyan; Nguyen, V.; Horikawa, T.; Nicholson, D. (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2015)
We analyse in detail our experimental data, our simulation results and data from the literature, for the adsorption of argon, nitrogen, carbon dioxide, methanol, ammonia and water on graphitized carbon black (GTCB), and show that there are two mechanisms of adsorption at play, and that their interplay governs how different gases adsorb on the surface by either: (1) molecular layering on the basal plane or (2) clustering around very strong sites on the adsorbent whose affinity is much greater than that of the basal plane or the functional groups. Depending on the concentration of the very strong sites or the functional groups, the temperature and the relative strength of the three interactions, (a) fluid-strong sites (fine crevices and functional group) (F-SS), (b) fluid-basal plane (FB) and (c) fluid–fluid (FF), the uptake of adsorbate tends to be dominated by one mechanism. However, there are conditions (temperature and adsorbate) where two mechanisms can both govern the uptake. For simple gases, like argon, nitrogen and carbon dioxide, adsorption proceeds by molecular layering on the basal plane of graphene, but for water which represents an extreme case of a polar molecule, clustering around the strong sites or the functional groups at the edges of the graphene layers is the major mechanism of adsorption and there is little or no adsorption on the basal planes because the F-SS and FF interactions are far stronger than the FB interaction. For adsorptives with lower polarity, exemplified by methanol or ammonia, the adsorption mechanism switches from clustering to layering in the order: ammonia, methanol; and we suggest that the bridging between these two mechanisms is a molecular spill-over phenomenon, which has not been previously proposed in the literature in the context of physical adsorption.